TRAINING ON PREPARING SIMPLE FINANCIAL REPORTS BASED ON ANDROID FOR UMKM IN SUBANG DISTRICT, WEST JAVA - Anggraini, Anggun; Kurniawan, Prasetyo; Amelia, Rizka Wahyuni; Imbron, Imbron; Pranowo, Agus Setyo; Muharam, Hari; Sasongko, Hendro; Yusnita, Nancy (International Journal of Engagement and Empowerment (IJE2), 2024)
The purpose of this Community Service activity is to train MSMEs in Subang Regency, West Java, to prepare simple Android-based financial reports. This program also aims to encourage participants to educate their surroundings and align with the demands of the millennial era. Using group discussions, the counseling session equips MSMEs with the knowledge to manage finances efficiently through Android-based tools. The activity includes motivational sessions by resource persons to enhance entrepreneurial spirit, demonstrations on creating business products, and hands-on training in preparing financial reports. These efforts not only foster financial literacy but also empower MSMEs to improve their business operations and sustainability. By integrating technology into financial management, the program supports MSMEs in adapting to modern business demands, increasing their competitiveness in the digital economy, and creating a ripple effect of education and innovation within their communities